2009
DOI: 10.1016/j.neuroscience.2009.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue thermogenesis heats brain and body as part of the brain-coordinated ultradian basic rest-activity cycle

Abstract: Brown adipose tissue (BAT), body and brain temperatures, as well as behavioral activity, arterial pressure and heart rate, increase episodically during the waking (dark) phase of the circadian cycle in rats. Phase-linking of combinations of these ultradian (<24 hour) events has previously been noted, but no synthesis of their overall interrelationships has emerged. We hypothesized that they are coordinated by brain central command, and that BAT thermogenesis, itself controlled by the brain, contributes to incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(110 citation statements)
references
References 61 publications
7
97
0
2
Order By: Relevance
“…Instrumented rats were transferred to the residence cage and housed individually for at least 1 day before the intruder experiments were conducted. During this 24-h period the resident rat displayed episodic ultradian increases in BAT, body, and brain temperatures preceding food intake, with episodes occurring at ϳ90-min intervals as we previously reported (3,46). We introduced the intruder rat during the dark phase ϳ20 min after the end of a meal when the rat was inactive and BAT, body, and brain temperatures were at low levels.…”
Section: Animals Used and Anesthesia For Implantation Of Thermistorsmentioning
confidence: 90%
See 2 more Smart Citations
“…Instrumented rats were transferred to the residence cage and housed individually for at least 1 day before the intruder experiments were conducted. During this 24-h period the resident rat displayed episodic ultradian increases in BAT, body, and brain temperatures preceding food intake, with episodes occurring at ϳ90-min intervals as we previously reported (3,46). We introduced the intruder rat during the dark phase ϳ20 min after the end of a meal when the rat was inactive and BAT, body, and brain temperatures were at low levels.…”
Section: Animals Used and Anesthesia For Implantation Of Thermistorsmentioning
confidence: 90%
“…In the present study we observed the resident rat for at least 24 h, recording the coordinated behavioral and physiological events that occur when the rat engages with the external environment as part of the basic rest-activity cycle (2,3,46,47). This enabled us to introduce the intruder rat when temperatures were at a basal level.…”
Section: Bat Thermogenesis Contributes To Emotional Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…A well-recognized metabolic adaptation to fasting is the reduction in heat production [6,7], accompanied by reductions in T b , usually through progressive declines during the inactive period [8][9][10][11][12][13][14], which have been argued to result from a regulated thermoregulatory response [8,9,15,16]. Fluctuations in T b can result from changes in set point [17,18], changes in activity [19,20] or changes in thermal conductance [21]. In birds, regional heterothermy during fasting may provide an explanation for why core T b does not vary much with fasting in some species, despite a large metabolic suppression [21].…”
Section: Introductionmentioning
confidence: 99%
“…Although these fluctuations may simply appear to be noise, they have important physiological signatures (e.g. insulin and growth hormone show pulsatile secretion in phase with T b fluctuations [24,25], fluctuations in core T b of quail are associated with changes in fuel use [26], alterations in hippocampal activation precedes thermogenic fluctuations [19,20]). As altered vigilance behaviours (i.e.…”
Section: Introductionmentioning
confidence: 99%